The effect of basic psychological needs on employees’ behavioral intention to protect industrial technology in high-tech firms - Lee, Sangwoo; Kim, Boyoung; Ivan, Ureta Vaquero (International Journal of Innovative Research and Scientific Studies, 2025)
As high-tech companies become increasingly important globally, these companies dedicate greater resources to robust technology security and leakage-prevention measures. This study aims to define the factors influencing autonomy, competence, and relatedness which are the basic psychological needs that influence the information leakage-prevention behaviors of employees in high-tech industry enterprises based on self-determination theory (SDT). Additionally, this empirical study investigates the influence of these factors on the behavioral intentions related to industrial technology leakage prevention. It analyzes the relationship between basic psychological needs and intrinsic and extrinsic motivation based on SDT. Moreover, it verifies the mediating effect of motivation on the relationship between basic psychological needs and behavioral intentions. An online survey was conducted among employees of high-tech industries in Korea resulting in the collection of 200 questionnaires. The analysis demonstrated that autonomy, competence and relatedness had a significant positive effect on intrinsic motivation. It means that intrinsic motivation plays a more critical role than extrinsic motivation in shaping the behavioral intention of high-tech firms to prevent industrial-technology leakage. However, no effect was observed for relatedness on extrinsic motivation or for extrinsic motivation on behavioral intentions. The findings indicate that autonomy negatively impacted extrinsic motivation. This suggests that in the high-tech technology sector, employees’ intrinsic motivation primarily drives their technology security behaviors based on personal professional judgment and ethics rather than extrinsic motivation.